Patient positioning... (A ready-reference guide) - McLellan, Marielle (Operating Room Nurses Association of Canada Journal, 1989)
Proper patient positioning is an important surgical consideration. Positioning is a key factor in accessing and exposing the operative site. There are also key safety factors implicated. Such functions as circulation and respiration as well as neuromuscular status can be compromised if the patient is improperly positioned. It is incumbent upon the O.R. nurse to be fully aware of the interventions and rationale behind the various patient positions. The following fundamentals of positioning have been developed as a guide. They were compiled by Marielle McLellan, Clinical Co—ordinator, Rockyview General Hospital in Calgary, where they have been implemented as a standardized reference for operating room staff.